INTEGRATING TBLT AS AN EFFECTIVE APPROACH OF ENGLISH INSTRUCTION FOR BUSINESS ENGLISH - Eshchanova G.E. ,; Nuratdinova N.B. , (Journal of new century innovations, 2022)
Annotation: This article discusses the integration of language learning methodology based on TBLT for Business English. The article defines deals with the term Business English as one of the ESP profiles (English for Specific Purposes).